MOF-derived hollow NiCo2O4 nanowires as stable Li-ion battery anodes. Issue 31 (23rd July 2020) - Chu, Kainian; Li, Zhiqiang; Xu, Shikai; Yao, Ge; Xu, Yang; Niu, Ping; Zheng, Fangcai
Abstract : Binary metal oxides with high theoretical specific capacities and power densities are promising anode materials for lithium-ion batteries but their poor cycling stability and huge volume expansion limit their extensive application in practical electrode materials. Abstract : Although binary metal oxides with high theoretical specific capacities and power densities are widely investigated as promising anode materials for lithium-ion batteries (LIBs), their poor cycling stability and huge volume expansion largely limit their extensive application in practical electrode materials. Herein, we report a facile strategy to synthesize hollow NiCo2 O4 nanowires through direct calcination of binary metal–organic frameworks (MOFs) in air. When evaluated as an anode material for LIBs, NiCo2 O4 nanowires deliver a reversible capacity of 1310 mA h g −1 at a current density of 100 mA g −1 after 100 cycles. Even at a high current density of 1 A g −1, NiCo2 O4 nanowires exhibit long-term cycling stability with a capacity of 720 mA h g −1 after 1000 cycles. The outstanding lithium-storage performance can be attributed to the unique structures with 1D porous channels, which are beneficial for the fast transfer of Li + ions and electrolyte and alleviate the strain caused by the volume expansion during cycling processes.